Online booking hotel : The effects of brand image, price, trust and value on purchase intentions / Dayang Siti Fazilah Awang Yakup - Awang Yakup, Dayang Siti Fazilah (2016)
People nowadays prefer to book hotel online compare to walk -in to the hotel. Online booking hotel can save time and cost especially for the working people. This research examines the effect of brand image, price, trust and perceived value on customer’s booking intentions. The result of this research are consistent with the findings from previous studies. From this research outcomes trust is the factor that give higher influence on customer’s purchase intentions. However, brand image, price and perceived value also give the positive results which also will influence purchase intentions among the Malaysia customer’s.